An emerging infectious cause of renal impairment in the UK. (15th November 2011) - Fhogartaigh, Caoimhe Nic; Newsholme, William; Kinirons, Mark; Tong, William
Abstract : Hantaviruses are endemic in many central European countries, particularly the Balkans, infection causing non-specific 'flu-like symptoms and renal dysfunction which is self-limiting in the majority of cases. In this case, there was a diagnostic delay, resulting in numerous unnecessary investigations, prolonged hospital stay and almost an invasive renal biopsy. A travel history is therefore essential, to establish travel to an endemic region within the previous 2–6 weeks. With increasing travel and immigration, hantavirus is likely to be seen more frequently as an imported infection into the UK. However, further research is required to establish the potential for acquisition of infection here, as the animal host, the bank vole, is part of local wildlife. Therefore, the authors urge physicians to be alert to this possibility when faced with acute renal failure in association with an undiagnosed febrile illness, particularly when there is a history of an appropriate environmental or animal exposure.